Internal Revenue Leakages Prevention and Control in the Local Government System (Global Journal of Management and Business Research, 2014)
The essence of fund control, cash flow management and fraud detection is to avoid wrong payment, improper and use of funds in the management of local government money. Funds Control Techniques are the products of statute (Acts, Decrees, Edict and Bye-Laws) and Regulations. They may be financial or administrative. The State funds are largely governed by the Public. Administration Law and Financial Instructions issued from time to time through circulars. This paper argues that Local Government Fund Control is largely governed by the provisions of Financial Memoranda. All issues of inadequate fund in the local government revolve around this particular internal revenue leakage and pose very serious threat to the entire existence of local government. This calls for urgent attention to eradicate this unfortunate phenomenon in our body polity. We have strong conviction if all the suggestions we offered in this paper are strictly adhered to the issue of internal revenue leakage will disappear to a vanishing point. It is only then that we can bark of having the real impact local government.
Keywords: financial memoranda; fund control; internal revenue leakage; corruption; local government; funds control techniques; financial malpractices; fraud; ac